Association of depression with all-cause and cardiovascular mortality among US adults with high and low baseline risk of cardiovascular disease. (February 2023) - Yang, Hui; Sun, Di; Yang, Yating; Lin, Ruilang; Xu, Jiaqin; Wu, Jingyi; Cui, Xiaorui; Li, Jiong; Qin, Guoyou; Han, Xiaojie; Yu, Yongfu
Highlights: Depression was associated with all-cause mortality among persons at high baseline risk of CVD. Depression was not statistically significantly associated with all-cause mortality in people at low baseline risk of CVD, which may be due to small number of events. Depression was statistically significantly associated with all-cause and CVD mortality in adults with different baseline risks of CVD. Abstract: The intervention of depression was considered a prevention and treatment option for cardiovascular disease (CVD). However, evidence regarding whether association of depression with mortality differed among people at high or low risk of CVD yielded conflicting results. We aimed to investigate associations between depression and all-cause and CVD mortality among 3854 and 3044 US adults at high and low baseline risk of CVD, respectively. Among participants at high risk of CVD, depression and per 5-point increase in PHQ-9 score were associated with 81% (HR=1.81, 95%CI: 1.15–2.86) and 33% (HR=1.33, 95%CI: 1.14–1.55) increased all-cause mortality, respectively. We did not find statistically significant associations between depression (HR=1.40, 95%CI: 0.67–2.95) and PHQ-9 score (HR=1.28, 95%CI: 1.00–1.63) with CVD mortality due to a small number of mortality events. Among people with low risk of CVD, each 5-point increment in PHQ-9 score was associated with all-cause mortality (HR=1.26, 95%CI: 1.02–1.56), while there was no statistically significant association of depression with all-cause mortality (HR=1.69, 95%CI: 0.75–3.81) and CVD mortality (HR=1.99, 95%CI: 0.83–4.81). This study found that depression was associated with all-cause mortality among individuals at a high baseline risk of CVD, but no significant association was observed in people at a low baseline risk of CVD.